Four consecutive coral bleaching events in the Northern Persian Gulf: 2014-2017 - Javid Kavousi; Parviz Tavakoli-Kolour; Sanaz Hazraty-Kari; Forough Goudarzi (Annals of Marine Science - Peertechz Publications, 2021)
Climate change-induced bleaching is a serious threat to coral reefs worldwide. In recent years, the number of repeated extensive bleaching events has increased globally. Here, we present four consecutive bleaching events and post-bleaching mortalities from four sites on Hormuz and Larak Islands, Iran, in the Persian Gulf from 2014 to 2017. The high thermotolerance of the corals and their endosymbiotic algae and the strong water currents and sites' turbidity could not protect the majority of the corals against bleaching. Back-to-back bleaching events left almost no unbleached coral colony at any site by 2017. Despite that, coral mortality did not increase at the sites of Hormuz Island that may be a sign of the fast recovery of the Persian Gulf corals after each bleaching event. However, the abundance of coral colonies with 81%-100% mortality at the sites of Larak Island that was constantly minimal in the first three years significantly increased in 2017. Considering bleaching and mortality responses, and abundance dynamics of the coral genera at the study sites, it seems that Dipsastraea at the southwest of Larak Island was a short-term winner; despite facing widespread moderate bleaching (i.e., < 50 of a colony was bleached) in 2014-2016, it managed to significantly increase its population in 2015 and 2016. However, in 2017, when almost all colonies were severely bleached (i.e., > 50 of a colony was bleached), there was a non-significant 27% reduction in its abundance. Dipsastraea at the north of Larak Island also survived in the first three years, but > 66% of its colonies showed 81%-100% mortality in 2017. Such findings warn that the aforementioned successes by corals are unlikely to persist under annual severe bleaching as is predicted for coming decades.